FEASIBILITY AND PRACTICALITY ANALYSIS OF AUGMENTED REALITY (AR) AS A SCIENCE LEARNING MEDIA IN ELEMENTARY SCHOOLS - Muttakin, Muttakin; Dewi, Ucia Mahya; Sari, Arlin Maya (Chimica Didactica Acta, 2024)
Information and communication technology should be integrated into the learning process to enhance the quality of education. One of the technologies that can be utilized is Augmented Reality (AR). AR media can help students learn complex concepts through interactive 3D visualizations of science topics. In the study, a science learning media based on mobile Augmented Reality (AR) technology was developed using the 4-D model (Define, Design, Develop, Disseminate). This study aimed to validate the feasibility and practicality of mobile augmented reality (AR) based science learning media. Lecturers, teachers, and students tested the feasibility and practicality of the media. The media validation test conducted by two lecturers resulted in a score of 92.26%, while the subject matter validation test by lecturers and students yielded a score of 97.84%. The developed AR media was also classified as highly practical, with the teacher and student questionnaires scoring 91.07% and 88.33%, respectively. The validity assessments of this AR media indicate that both the media and the subject matter fall into the "Highly Feasible" and "Highly Practical" categories for use as science learning media in elementary schools. The students response to using this media in learning is very good. Students are enthusiastic about participating in learning and enhancing their curiosity.